Kemampuan Koneksi Matematika dalam Pembelajaran Kesetimbangan Kimia - Hilda, Lelya (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
Mathematical connection is the ability of mathematics to connect conceptual and procedural knowledge, use mathematics in other subjects, use mathematics in life activities. Mathematics is a difficult subject for students as well as chemical equilibrium material, because both lessons are abstract. Mathematical ability is a basic ability that students must master in Chemical Equilibrium. Determination of Equilibrium Assets (Kc and Kp) requires mathematical connection capabilities. The results obtained from the Chemical Equilibrium test given are still low with a percentage of 65% for the calculation of removal, 45% root shape and the ability to multiply and divide the decimal number to 67%. This is because learning mathematics and chemical equilibrium are difficult subjects so students are less interested.